The implementation of good university governance in the state universities - Wardhani, Rulyanti Susi; Taufik, Taufik; Fuadah, Luk luk; Siddik, Saadah (Jurnal Organisasi dan Manajemen, 2019)
The purpose of this study was to determine the differences in the application of good university governance in South Sumatra and Bangka Belitung State Universities, while the state universities were Bangka Belitung University, Sriwijaya University, Sriwijaya State Polytechnic, Bangka Belitung Manufacturing Polytechnic. The principles of good university governance in this study are governance structure, autonomy, accountability, leadership, and transparency. Respondents from the study are structural officials in the form of questionnaires. The analysis used Friedman different test because groups of state universities that are new and long established, the results of the analysis that accountability and transparency in the application of good university governance between Bangka Belitung University and Sriwijaya University are different, unlike the Sriwijaya Polytechnic with the Bangka Belitung Manufacturing Polytechnic in the application of good university governance has no difference.